COVID-19-Associated Invasive Pulmonary Aspergillosis in the Intensive Care Unit: A Case Series in a Portuguese Hospital - Ranhel, David (2022)
Invasive pulmonary aspergillosis (IPA) has become a recognizable complication in coronavirus disease 2019 (COVID-19) patients admitted to intensive care units (ICUs). Alveolar damage in the context of acute respiratory distress syndrome (ARDS) appears to be the culprit in facilitating fungal invasion in COVID-19 patients, leading to a COVID-19-associated pulmonary aspergillosis (CAPA) phenomenon. From November 2020 to 15 February 2021, 248 COVID-19 patients were admitted to our ICUs, of whom ten patients (4% incidence) were classified as either probable (six) or possible (four) CAPA cases. Seven patients had positive cultural results: Aspergillus fumigatus sensu stricto (five), A. terreus sensu stricto (one), and A. welwitschiae (one). Five patients had positive bronchoalveolar lavage (BAL) and galactomannan (GM), and two patients had both positive cultural and GM criteria. All but two patients received voriconazole. Mortality rate was 30%. Strict interpretation of classic IPA definition would have resulted in eight overlooked CAPA cases. Broader diagnostic criteria are essential in this context, even though differentiation between Aspergillus colonization and invasive disease might be more challenging. Herein, we aim to raise awareness of CAPA in view of its potential detrimental outcome, emphasizing the relevance of a low threshold for screening and early antifungal treatment in ARDS patients.